Artificial Intelligence and the Future of the International System: international and political journal - Ali, Assistant Lecturer Muhammad Ali Abbas (The International and Political Journal, 2025)
Artificial intelligence has been integrated into various aspects of life, serving as a driving force in the global system. It gives rise to new actors in the form of technological entities and elevates the status of individual talents, as a result increasing the significance of the individual within the global system and shifting the balance of power. Furthermore, it enhances the capacity of corporations to access novel weapons of mass destruction embodied in AI. Artificial intelligence is going to directly impact the economy in terms of employment, efficiency, and the increased value of knowledge-based economies, placing rentier states in a precarious position. The expanding influence of technology on social life and legal systems constitutes a significant challenge, necessitating a redefinition of privacy, democracy, individual rights, authority, state sovereignty, security, reliability, as well as conflict.